Retreat-site selection in the common flat lizard (Platysaurus intermedius) - Egan, Lorraine (My University, 1997)
Numerous studies have shown that reptiles are able to assess their environment and select retreat sites based upon this assessment. Two main reasons proposed to explain retreat choice are predator avoidance and thermoregulation. In my study, I conducted laboratory experiments ,)0 16 Platysaurus intermedius in all attempt to elucidate what cues are used in retreat site selection in these lizards ..Platysaurus intermedius use rock crevices as retreats and I tested whether crevice height, depth and the thickness of the roof were important cues. I also measured selected body temperature in a thermal gradient Field measurements of lizard body temperature as well as crevice temperature of retreats not used by the lizards were recorded and compared. Platysattrus intermedius show a significant preference for narrow and deep retreats. This would appear to reflect an efficient anti-predatory tactic with minor potential thermoregulatory consequences ..Potential predators observed in the field would be unable to gain access to these lizards during the period that they are sequestered. No significant differences in retreat or temperature selection (in the laboratory experiments) by different age groups or different sexes were observed. However, temperatures selected in the laboratory were considerably higher than those available in the field. This observation possibly reflects an environmentally imposed limitation to thermoregulation to lizards in the field. Field recordings of lizard body temperature (when inside retreats) and the temperature of retreats not used by p. intermedius revealed that occupied crevices had significantly higher temperatures than unoccupied crevices ..This indicates that P. intermedius may use temperature as an environmental cue by which to select a suitable retreat. It would thus appear that predation risks as well as thermoregulation are considerations for P. intermedius when selecting a retreat site, however it is difficult to say with any confidence whether predator avoidance or thermoregulation is of more importance.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 1997.
Keywords: Lizards